Analisis penggunaan media dalam pembelajaran tematik ditinjau dari teori belajar konstruktivisme di kelas V sekolah dasar - Annisa Rahmawati; Chumdari Chumdari; Karsono Karsono (Didaktika Dwija Indria, 2021)
This research aims to determine the use of learning media and constructivism learning theory during the learning activities. This research uses descriptive qualitative research metods and case study approach. Sources of data in this study was fifth grade teachers and fifth grade students of SDN Tunggulsari II Surakarta. The data collection technique was done by observing, interviewing and studying documents. The data were analyzed using the data analysis model of Miles and Huberman.The result of this study indicate that during online learning activities the teachers continues to use learning media to help provide teaching materials. The media used by the teachers was simplified and adapted due to the condition and facilities that student have. Constructivism learning theory during the learning includes the appearance of student looking for, exploring, and discovering new knowledge by themselves.The series of learning activites during the online learning implemented by the teacher was accordance with  2013 curiculum learning. The learning process that carried out by the teachers also reflects to tematic learning. The result of this study can also be used to increase teacher insight of the use of media during online learning and constructivism learning theory can be applied during learning to make student more active.